2012
DOI: 10.5194/acp-12-9321-2012
|View full text |Cite
|
Sign up to set email alerts
|

On dithiothreitol (DTT) as a measure of oxidative potential for ambient particles: evidence for the importance of soluble transition metals

Abstract: Abstract. The rate of consumption of dithiothreitol (DTT) is increasingly used to measure the oxidative potential of particulate matter (PM), which has been linked to the adverse health effects of PM. While several quinones are known to be very reactive in the DTT assay, it is unclear what other chemical species might contribute to the loss of DTT in PM extracts. To address this question, we quantify the rate of DTT loss from individual redox-active species that are common in ambient particulate matter. While … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

47
471
6
5

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 376 publications
(529 citation statements)
references
References 45 publications
47
471
6
5
Order By: Relevance
“…4 assuming the redox activities are additive, as was reported for quinone species in the supporting information of Charrier and Anastasio (2012). There is a strong correlation between the predicted and observed DTT decay rates (r 2 = 0.87).…”
Section: Redox Activity Prediction For Naphthalene Soasupporting
confidence: 57%
See 4 more Smart Citations
“…4 assuming the redox activities are additive, as was reported for quinone species in the supporting information of Charrier and Anastasio (2012). There is a strong correlation between the predicted and observed DTT decay rates (r 2 = 0.87).…”
Section: Redox Activity Prediction For Naphthalene Soasupporting
confidence: 57%
“…In one such study researchers found that hydrogen peroxide generation from the DTT assay performed on particles from Fresno, California, could be accounted for by measuring the aerosol mass loadings of 9,10-phenanthrenequinone, 1,2-naphthoquinone, and 1,4-naphthoquinone (Chung et al, 2006). In another study, by assigning the DTT loss rate to individual particulate species again from the Fresno area, Charrier and Anastasio were able to predict DTT decay as arising 80 % from transition metal species and 20 % from quinone species (Charrier and Anastasio, 2012).…”
Section: Introductionmentioning
confidence: 97%
See 3 more Smart Citations